Nurse Scheduling Problem Using Hybrid Simulated Annealing Algorithm - عبد الرزاق محمد صادق; هندي علي ابراهيم (Journal of Economics and Administrative Sciences, 2018)
Nurse scheduling problem is one of combinatorial optimization problems and it is one of NP-Hard problems which is difficult to be solved as optimal solution. In this paper, we had created an proposed algorithm which it is hybrid simulated annealing algorithm to solve nurse scheduling problem, developed the simulated annealing algorithm and Genetic algorithm. We can note that the proposed algorithm (Hybrid simulated Annealing Algorithm(GS-h)) is the best method among other methods which it is used in this paper because it satisfied minimum average of the total cost and maximum number of Solved , Best and Optimal problems. So we can note that the ratios of the optimal solution are 77% for the proposed algorithm(GS-h), 28.75% for Simulated annealing algorithm (SA), 35.7% for Improved Simulated annealing (SA*), 26.25% for Genetic algorithm ( GA) and 45.6% for Improved Genetic algorithm for all problems (2000 problems).